The Influence Of Islamic Social Capital And Islamic Financial Behavior On The Welfare Of Fishermen (Case Study Of Fishermen In Perupuk Village, Batu Bara Regency) - Sahri, Riadil Jannah; Marliyah, Marliyah; Daulay, Aqwa Naser (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the influence of Islamic Social Capital and Islamic Financial Behavior on the welfare of fishermen in Perupuk Village, Batu Bara Regency. This is a quantitative study using associative analysis. The sampling technique used is the saturated sample method, in which the entire population is used as research respondents. In this study, the population consisted of 95 fishermen, all of whom were included as the research sample. The data analysis techniques used include validity and reliability test, classical assumption test, and multiple linier regression analysis to examine the influence of the dependent variable. The result show that: 1) Islamic social capital and Islamic financial behavior have a significant influence, both partially and simultaneously, on the welfare of fishermen, indicating that social relationships, participation in religious activities, and the application of Islamic financial principles can improve the well-being of fishermen. 2) the influence of Islamic social capital reflects strong ukhuwah (brotherhood) and social solidarity among fishermen. Meanwhile, Islamic financial behavior reflects an awareness of sharia-based financial management. This indicates that Islamic values, when implemented in social life and financial behavior, make a tangible contribution to improving the welfare of fishermen. This study suggest that Islamic social capital and Islamic financial behavior play an important role in enhacing fishermen’s welfare. Therefore, policies that strengthen social networks and improve financial literacy and access to Islamic financial services for fishermen are needed.